Does anesthetic provide similar neuroprotection to therapeutic hypothermia after cardiac arrest? - Zhang, Hong (BioMed Central, 2010)
In the previous issue of Critical Care, Meybohm and colleagues provide evidence to support hypothermia as a kind of therapeutic option for patients suffering cardiac arrest. Although anesthetics had been used to induce hypothermia, sevoflurane post-conditioning fails to confer additional anti-inflammatory effects after cardiac arrest. Further research in this area is warranted.